A territorial community as a paradigm? - Arumäe, Urmas (Business: Theory and Practice, 2010)
In this article, the author provides a cursory introduction of the idea to base the interpretation of the functional mechanisms of territorial communities on Kuhn’s treatment of the paradigms of scientific communities. According to the author’s interpretation and treatment, territorial communities are human associations that are related to self-organizing territories, the sequence of timely states, which are being called a process. From this, it ensues that a territorial community is a process. Based on the author’s position and the context of territorial communities, paradigms can be explained as follows: the paradigms of territorial communities determine the important objects with which the community deals and the related problems and/or questions that are established and the methods whereby theses problems and/or questions are resolved.